The study of transgene intergration hotspots in mammalia expression system - Shamsuddin, Shaharum (Universiti Sains Malaysia, 2015)
Mammalian expression system is very crucial for the production of proteins in numerous scientific and commercial areas as they are able to perform proper protein folding as compared to other hosts. Matrix attachment regions (MARs) are concentrated with transcription factor binding sites and have a strong effect on the level of expression of transgenes, thus highly studied to increase protein production. In this study, an expression vector carrying green fluorescent protein was transfected into mouse myeloma NSO cell line in order to allow random integration of the vector into the host genome. Conceptually, if the vector is integrated into a transcriptionally active site within the genome, green fluorescent protein will be highly or constitutively expressed. Transfected cells were then subjected to sorting in order to select the high producing cells using ClonePix FL (CPL). CPL is an automated high-throughput clone selection instrument. DNA sequences in the genome flanking the integrated vector in the high producing cells were subsequently retrieved using ‘genome walking’ method. Following this, the flanking regions were sequenced and characterized using bioinformatics tools. Functional analysis was carried out by entering the sequences into three different programs (SMARtest, MARfmder and MARscan) to determine the presence of Matrix Attachment Regions. In addition, biochemical characterization was also done using Chromatin Immunoprecipitation (ChIP) Assay. As a result, putative MAR elements were identified in mammalian expression system with different lengths of MAR regions between the three algorithms. MARJnndiii proteins that were used in CMP assay were also shown to interact with the mouse